Enhancing Hotel Financial Reporting through Accounting Understanding and Information System Utilization: A Case Study of a 5-Star Resort in Bali - Putu Sita Ivania; Ni Luh Riska Yusmarisa; Ni Ketut Mareni (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The main objective of this paper is to determine the extent to which the financial statements quality within a 5-Star Resort in Bali is influenced by proficiency in accountancy and the employment of accounting information systems. In this investigation, the integrity of financial statements (Y) serves as the outcome variable, while erudition in accountancy (X1) and the application of accounting information systems (X2) function as the explanatory variables. To examine the influence of each explanatory element upon the outcome variable, the study employed a multiple linear regression technique. The individuals comprising the research cohort are personnel from the financial division of a 5-Star Resort in Bali. Saturated sampling was the sample strategy used in this study. All study participants received questionnaires, which served as the primary source of data. Hypothesis testing was performed using SPSS 26.0 for Windows. The results show that both accounting understanding and the utilization of accounting information systems have a positive and significant effect on financial statement quality, both individually and simultaneously. These findings highlight the importance of improving employee competence in accounting and optimizing the effectiveness of accounting information systems to produce reliable and high-quality financial reports. The study implies that strengthening human resource capacity and continuously updating technological systems can enhance financial transparency and accountability in the hospitality industry. In light of these results, management is advised to enhance accounting knowledge and enhance the information system in order to generate financial statements of higher quality.